Frailty status and altered glucose-insulin dynamics - Kalyani, Rita Rastogi; Varadhan, Ravi; Weiss, Carlos O; Fried, Linda P; Cappola, Anne R (The journals of gerontology. Series A, Biological sciences and medical sciences, 2012)
We examined women in their 80s and 90s and evaluated the hypothesis that abnormalities in the dynamic response of glucose and insulin to a glucose load are associated with frailty status. We performed a 75 g oral glucose tolerance test in 73 community-dwelling women aged 84-95 years without known diabetes enrolled in the Women's Health and Aging Study II. We examined the association of frailty status (nonfrail, prefrail, or frail) with oral glucose tolerance test glucose and insulin levels at 0, 30, 60, 120, and 180 minutes using multiple linear regression models. Using American Diabetes Association criteria, only 27% of older women had normal glucose status, 48% had prediabetes, and 25% had undiagnosed diabetes. Fasting glucose, fasting insulin, homeostasis model of assessment-insulin resistance, and Matsuda index were similar by frailty status, adjusting for age and body mass index. Conversely, mean oral glucose tolerance test glucose levels were higher at 60 minutes (44.6 ± 18.1 mg/dL higher) and 120 minutes (67.1 ± 23.5 mg/dL higher) and to a lesser extent at 180 minutes (44.3 ± 22.5 mg/dL higher) in frail versus nonfrail women as was integrated glucose area after adjustment. Mean 120-minute insulin level was also higher in frail versus nonfrail women (45.7 ± 22.4 μU/mL higher). Overall, glucose and insulin responses were more exaggerated and prolonged in frail versus nonfrail or prefrail women. Our data demonstrate dysregulation in response to glucose challenge as a component of physiologic vulnerability associated with frailty in old-old women. Future studies should examine the timing of abnormal glucose-insulin dynamics with respect to the pathogenesis of frailty.